Hemolytic Uremic Syndrome as a Cause of Adult Acute Renal Failure (Annals of Medical Research, 2021)
None
Keywords: Acute Renal Failure, Thrombotic Thrombocytopenia; Hemolytic-Uremic Syndrome, İntensive Care.